Unraveling small-scale defects in irradiated ThO2 using kinetic Monte Carlo simulations. (June 2022) - Jiang, Chao; He, Lingfeng; Dennett, Cody A.; Khafizov, Marat; Mann, J. Matthew; Hurley, David H.
Abstract: Point defects and their clusters generated through irradiation can have significant impact on the physical and mechanical properties of materials. However, direct experimental visualization of these small-scale defects using high-resolution scanning transmission electron microscopy remains a challenging task. Here, using thorium dioxide (ThO2 ) with the fluorite structure as a model system, we demonstrate the use of ab initio basin-hopping simulations in synergy with object kinetic Monte Carlo simulations as a powerful tool for identifying small defect complexes in irradiated materials. In addition to providing quantitative insights into defect evolution in ThO2 under irradiation, our study reveals an unexpected role of bound anti-Schottky defect clusters in mediating defect transport. Remarkably, despite their poor thermal stability against dissociation at high temperatures, the transient formation of bound anti-Schottky defects under irradiation and their subsequent migration provide the dominant mechanism for the growth of large interstitial loops that have been experimentally observed in ThO2 . Graphical abstract: Image, graphical abstract